Virtual currency in sanctioned jurisdictions: stepping outside of SWIFT. Issue 2 (1st July 2019) - Kirkpatrick, Katherine; Savage, Christine; Johnston, Russell; Hanson, Matthew
Abstract : Purpose: To understand and analyze sanctions evasion and enforcement via virtual currencies. Design/methodology/approach: Discusses various jurisdictions' attempts to further the use of virtual currency to facilitate and maximize access to international funds; analyzes the aspects that make virtual currency uniquely suited to evade sanctions; suggests best practices for industry participants to be sure to account for the differences in crypto asset structure and related risks. Findings: The US Treasury Department's Office of Foreign Assets Control (OFAC) has explicitly stated that despite virtual currency's anonymity, industry participants are still responsible for policing and enforcing client compliance. Although sanctioned jurisdictions are thinking creatively about ways around SWIFT, the use of virtual currency to skirt sanctions presents certain challenges. Practical implications: Virtual currency industry participants should understand OFAC's specific guidance regarding compliance obligations in the cryptocurrency space, and should implement best practices and conservative measures to avoid unknowingly running afoul of sanctions laws. Originality/value: Expert analysis and guidance from experienced investigations and sanctions lawyers.